ฺBook Review: The Public Policy Theory Primer (3rd Edition, 2017): By Kevin B. Smith and Christopher Larimer - มูลพงศ์, ธนากร (วารสารสังคมศาสตร์บูรณาการ มหาวิทยาลัยมหิดล, 2022)
The Public Policy Theory Primer is one of the essential must-read books for public policy and public administration students. An interesting feature of the book is that it introduces the reader to the essential concepts of public policy and sets out an important agenda for the future of policy studies. In this book, Professors Kevin B. Smith (University of Nebraska-Lincoln) and Christopher Larimer (University of Northern Iowa) divide the area of public policy studies into 7 dimensions: (1) relationships between policy and politics; policy process, or how governments create policies? (3) policy analysis, or analyzing problems and offering options; (4) policy evaluation, or assessing programs; (5) policy design, or how do policies distribute power and why? (6) relationships between policymakers and policymaking institutions; and (7) policy implementation, or how was a policy decision translated into action?